2012
DOI: 10.1165/rcmb.2011-0369oc
|View full text |Cite
|
Sign up to set email alerts
|

A Plasminogen Activator Inhibitor-1 Inhibitor Reduces Airway Remodeling in a Murine Model of Chronic Asthma

Abstract: We previously reported that plasminogen activator inhibitor (PAI)-1 deficiency prevents collagen deposition in the airways of ovalbumin (OVA)-challenged mice. In this study, we explored the therapeutic utility of blocking PAI-1 in preventing airway remodeling, using a specific PAI-1 inhibitor, tiplaxtinin. C57BL/6J mice were immunized with intraperitoneal injections of OVA on Days 0, 3, and 6. Starting on Day 11, mice were challenged with phosphate-buffered saline or OVA by nebulization three times per week fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…Tiplaxtinin (PAI-039), the most well studied small-molecule inhibitor, attenuates asthmatic episodes, reduces both hyperlipidemia and hyperglycemia, suppresses angiogenesis and has recently been identified as a potent inhibitor of carotid stenosis by stimulating vascular smooth muscle cell apoptosis [13][14][15][16][17][18][19][20]. Similarly, other compounds that share a similar binding site on PAI-1 as tiplaxtinin have been synthesized [21,22].…”
Section: Structure and Chemical Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tiplaxtinin (PAI-039), the most well studied small-molecule inhibitor, attenuates asthmatic episodes, reduces both hyperlipidemia and hyperglycemia, suppresses angiogenesis and has recently been identified as a potent inhibitor of carotid stenosis by stimulating vascular smooth muscle cell apoptosis [13][14][15][16][17][18][19][20]. Similarly, other compounds that share a similar binding site on PAI-1 as tiplaxtinin have been synthesized [21,22].…”
Section: Structure and Chemical Antagonistsmentioning
confidence: 99%
“…Since it is known that tiplaxtinin and TM5275 promote PAI-1 substrate behavior, however, these inhibitors may prevent the conformational change in β-sheet A of PAI-1 necessary to accommodate insertion of the PAI-1 RCL during the protease inhibition reaction [25]. If tiplaxtinin or TM5275 were to complex with PAI-1 at the vitronectin-binding site, it has been suggested that these inhibitors would not be effective since the majority of circulating PAI-1 is bound to vitronectin; nevertheless, the available data confirm significant in vivo efficacy for these drugs [13][14][15][16][17][18][19][20]27]. Figure 1.…”
Section: Structure and Chemical Antagonistsmentioning
confidence: 99%
“…PAI-1 is elevated in human asthma and promotes airway remodeling in murine asthma models (21, 2328). PAI-1 overexpression, triggered by viruses and allergens, is associated with airway fibrosis while PAI-1 deficiency protects mice from fibrotic airway remodeling (21, 2326, 29).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity of PAI-1 structure and function, several low-molecular weight antagonists of PAI-1 have been developed to evaluate specific contributions of this SERPIN to disease pathologies (7). Tiplaxtinin (PAI-039), one of the most well-studied small-molecule inhibitors, attenuates asthmatic episodes, hyperlipidemia, hyperglycemia and angiogenesis (714).…”
Section: Pai-1 Structure/functionmentioning
confidence: 99%
“…Tiplaxtinin (PAI-039), one of the most well-studied small-molecule inhibitors, attenuates asthmatic episodes, hyperlipidemia, hyperglycemia and angiogenesis (714). The specific mechanism by which tiplaxtinin antagonizes the anti-fibrinolytic activity of PAI-1 involves promotion of a substrate-like conformation resulting in PAI-1 cleavage and impaired uPA and tPA inhibition (15,16).…”
Section: Pai-1 Structure/functionmentioning
confidence: 99%